Fluoride - Fairweather-Tait, Susan (Henry Stewart Talks, 2025)
Function of fluoride in the body, Function in bone and teeth, Dietary sources, Absorption and distribution of fluoride, Deficiency and excess fluoride levels, Dental Caries, Dietary reference values for fluoride